Role Playing for Islamic Values in Early Childhood: An Islamic Education Management Approach - Riandini, Monika; Puspitasari, Tuti; Sumarni; Sundari, Las; Al Fathan, Kukuh Maulana (Journal of Advanced Islamic Educational Management, 2025)
This study examined the effectiveness of the role-playing method in improving the understanding and internalization of basic Islamic values-especially honesty, discipline, politeness, helping, and love of cleanliness-in 31 students of class A/B RA Raudlatul Huda Sukarendah. The researcher implemented a two-cycle classroom action research with a descriptive qualitative approach. Data were collected through observation, field notes, documentation, and attitude assessment, then analyzed thematically with source triangulation. Results showed significant improvement: contextual understanding of Islamic values rose from 35% to 88%, while behavior according to these values increased from 20% to 83% after two cycles. This success reflects the application of Islamic education management principles that are responsive to children's nature, integrate values in curricular planning, and apply character-based holistic assessment. The researcher recommends the integration of participatory methods such as role play as an innovative practice in the management of transformative Islamic learning in early childhood education institutions.